Eccrine cylindroma of the face and scalp - Manicketh, Indu (Indian Dermatol Online J, 2016)
Cylindroma is a benign skin adnexal tumor of eccrine differentiation. Clinically, they are disfiguring lesions that can mimic a malignancy. Cylindromas can be single or multiple and commonly involve the scalp (turban tumor) and face. Multiple cylindromas can have a syndromic association as seen in Brooke–Spiegler syndrome and familial cylindromatosis. We present a case of non familial cylindroma of the face that clinically mimicked a basal cell carcinoma. The histopathology was confirmatory. Herein we also highlight the utility of a simple and inexpensive histochemical stain Periodic Acid Schiff in supporting the diagnosis.